EFEKTIVITAS PENGAWASAN TINGKAT KESEHATAN PERBANKAN DI TIMOR-LESTE DENGAN METODE CAMEL: 2004.Q1-2010.Q4 - , Ana Paula Amaral, Dr. Muhammad Edhie Purnawan, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bank is an institution which its main activity is funded rising from society then revolves around it with the purpose to generate revenue from which. Therefore, it is important for bank to maintain soundness because the business activity is related to banking performance. The purpose of this research was to prove soundness or to compare the performance of the Bank as measured by CAMEL. The objective of the researched by third foreign bank and local bank, which works in Timor-Leste during 2004-2010. The types of researched was used testing hypotheses (hypotheses), while the hypothesis has been included in the hypothetical corelation. In this research, the strategi data collection used in the form of filing (archived), i.e. the data collected from records or databases that already exist. There is infromation of technology of date base collection from data base. The results showed that an average to calculate the value of the three branches of foreign banks with an average of 30 percent for CAR. There is following ROA from 2004 to 2010 too many nouns changes drastically from the average of 2 percent. Operating expenses and operating income (BOPO) from 2004 to 2010 changed for each year the average of 46 percent. There is the ratio of liquidity for each bank the ratios are more than standard where the average of 66,4 percent. The six of components of CAMELS the four componen which investigated and noted that there is in the component has a ranking below the rate or bad.